2005
DOI: 10.1002/rcm.2022
|View full text |Cite
|
Sign up to set email alerts
|

Development of a liquid chromatography/tandem mass spectrometry method for the quantification of fumonisin B1, B2 and B3 in cornflakes

Abstract: A liquid chromatography/tandem mass spectrometry (LC/MS/MS) method for the determination of fumonisin B1 (FB1), B2 (FB2) and B3 (FB3) in cornflakes is described. During method development, special attention was paid to the selection of a suitable internal standard (IS) in order to offer a good alternative for deuterated FB1. In this respect, the C12-sphinganine analogue (2S,3R)-2-aminododecane-1,3-diol was chosen because of its structural similarity to the fumonisin backbone and its chromatographic elution bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 41 publications
(55 reference statements)
2
17
0
Order By: Relevance
“…It can also be seen from Table 3 that IACs have been successfully used by laboratories, where only TLC is available [44,45,47], and the improved clean-up means that the lack of separation on the TLC plate becomes less disadvantageous. At the other end of the spectrum IAC clean-up has been used with sophisticated chromatographic end-determinations being used in LC/MS and LC/MS/MS [107,108].…”
Section: Application Areas For Iac Clean-upmentioning
confidence: 99%
“…It can also be seen from Table 3 that IACs have been successfully used by laboratories, where only TLC is available [44,45,47], and the improved clean-up means that the lack of separation on the TLC plate becomes less disadvantageous. At the other end of the spectrum IAC clean-up has been used with sophisticated chromatographic end-determinations being used in LC/MS and LC/MS/MS [107,108].…”
Section: Application Areas For Iac Clean-upmentioning
confidence: 99%
“…In this regard, the most critical step is the extraction that should allow good recoveries for all mycotoxins under investigation in the specific food matrix. Several authors have reported that high methanol or acetonitrile concentrations (≥75%) in the extraction solvent are suitable for the extraction of most mycotoxins, such as trichothecenes, ZEA, OTA, and AFs,6–9 whereas high extraction efficiencies for FBs can be obtained by increasing the water fraction and/or lowering the pH of the extraction mixture 10–12…”
mentioning
confidence: 99%
“…Until now no isotopically labeled internal standards have been used in multi‐mycotoxin LC/MS/MS methods. Another approach is the use of structural analogues such as the sphinganine analogue (2 S ,3 R )‐2‐aminododecane‐1,3‐diol to determine FB 1 , FB 2 and FB 3 in corn‐flakes 1, 22. The use of verrucarol was reported to determine Fusarium toxins 23.…”
Section: Resultsmentioning
confidence: 99%